2019
DOI: 10.1002/mame.201800726
|View full text |Cite
|
Sign up to set email alerts
|

Effective Control of Laser‐Induced Carbonization Using Low‐Density Polyethylene/Polystyrene Multilayered Structure via Nanolayer Coextrusion

Abstract: Controlled carbonization is very critical in improving the effect of laser‐induced patterns on a polymer surface. In the present work, the effects of a multilayered structure on the physical and laser‐marking properties of a low‐density polyethylene/polystyrene (LDPE/PS) multilayered film are studied. The multilayered film is prepared using nanolayer coextrusion and treated in air by scanning with a neodymium‐doped yttrium aluminum garnet (Nd:YAG) pulsed laser beam. Based on various analyses, the laser‐induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
(49 reference statements)
0
7
0
Order By: Relevance
“…Laser marking is characterized by noncontact processing. The laser with a wavelength of 1064 nm is a more commonly used laser in the industry and is suitable for materials such as metal, ceramics, wood, and plastic. Compared with the easy carbonization and high char residue features of polycarbonate and polystyrene, it is rather difficult to perform laser marking with PP itself due to the poor absorption of the near-infrared laser energy of the 1064 nm wavelength. Usually, the method of adding laser marking additives can effectively improve the laser marking performance of PP.…”
Section: Introductionmentioning
confidence: 99%
“…Laser marking is characterized by noncontact processing. The laser with a wavelength of 1064 nm is a more commonly used laser in the industry and is suitable for materials such as metal, ceramics, wood, and plastic. Compared with the easy carbonization and high char residue features of polycarbonate and polystyrene, it is rather difficult to perform laser marking with PP itself due to the poor absorption of the near-infrared laser energy of the 1064 nm wavelength. Usually, the method of adding laser marking additives can effectively improve the laser marking performance of PP.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the variety of properties of plastics, marking them is in many cases difficult or completely impossible. Easy carbonization and high carbon content make materials such as polycarbonate [35] and polystyrene [36] highly susceptible to marking with the use of radiation at the wave length λ = 1064 nm. Because of low light absorption at the same wavelength, marking elements made of polyethylene [37] and polypropylene [38] requires the use of laser marking additives (LMAs).…”
Section: Introductionmentioning
confidence: 99%
“…Research and development of simple, convenient, low-cost, and environmentally friendly ABS laser marking materials for its application is very important. From many studies, it is observed that polypropylene (PP)-, polyethylene (PE)-, and polyacrylamide (PAM)-based hydrogel materials are insensitive to the near-infrared laser with 1064 nm wavelength, difficult to absorb laser energy, and cannot produce high definition and contrast laser marking text and patterns. In order to solve the problem of poor absorption of the near-infrared laser by such materials, laser-sensitive inorganic particles, such as graphene, multilayer graphene, tin dioxide, antimony (III) oxide, bismuth oxide, , magnetic particles, carbon nanotubes, etc., are introduced into the polymer materials and can effectively absorb near-infrared laser energy and convert it into heat, resulting in polymer carbonization or formation of foam, which contributes to the black or light markings on the material surface.…”
Section: Introductionmentioning
confidence: 99%